Dye-sensitised Photo-dimerisation of Mandelic Acid by Singlet Oxygen - C. Ameta, Suresh; P.B. Punjabi, (Mrs.); Neeta Mangal , (Miss); Jain, P.K.; Shashi K. Agarwal, (Mrs.) (Asian Journal of Chemistry, 2010)
Dye-sensitized photo-dimerisation of mandelic acid has been carried out. The product has been isolated and characterized. The participation of singlet oxygen as the active species has also been confirmed. A tentative mechanism for the photo-dimerisation of mandelic acid by singlet oxygen has been proposed.